All Stars Sparkle: As a Result of Hard Work. - Hilton, Anne (Trinidad Guardian)
A review of the concert Classical Jewels V with live performance by Catelli All Stars Steel Orchestra. The high points of the concert were Mozart's Concerto in A for clarinet and Telemann's Sonata in B minor. The musical director was Gerry Jemmott and guest conductors Pat Bishop and Paul Hill.
Keywords: Steel bands (Music) -- Trinidad and Tobago; Steel band music -- Trinidad and Tobago; Musicians -- Trinidad and Tobago